Total LDH and isoenzyme pattern in crossbred dairy cows during lactation - SATHYBAMA, T; LEELA, V; VISWANATHAN, S; GAJENDRAN, K (The Indian Journal of Animal Reproduction, 2023)
Estimation of total LDH and fractionation of isozymes by PAGE were done in the sera of dairy cattle. The level was 696.00 ± 22.97 IU/L during late lactation and 609.50±_24.17 IU/L during early lactation. The non- lactating animals showed a value of 435.88 ± 22.14 IU/L. Among the isozymes, LDH 1 decreased, whereas LDH 3,4 & 5 showed an increase during early lactation. The values were also estimated during 1st and 3 subsequent lactations and a non-significant fall was observed. Among the isozymes, LDH 1 showed an increase and LDH 3,4 and 5 recorded a decrease.